Early differentation of lamellar structure of the intervertebral disc in staged human embryos - Woźniak, Witold; Grzymisławska, Małgorzata; Łupicka, Joanna; Bruska, Małgorzata; Piotrowski, Adam; Gałązka, Anna; Rojewska, Magdalena; Sobański, Jarosław (Journal of Medical Science, 2015)
Introduction. In the vast literature concerning the development of the intervertebral discs controversies exist as to the period of differentiation and structure of the nucleus pulposus and annulus fibrosus. These controversies result from different determination of age of the investigated embryos. Aim. Using embryos from departmental collection age of which was established according to international Carnegie staging and expressed in postfertilizational days, the differentiation of the intervertebral discs was traced. Material and methods. Study was performed on 34 embryos at developmental stages 13–23 (32–56 days). Embryos were serially sectioned in sagittal, frontal and horizontal planes. Sections were stained with various histological methods and impregnated with silver. Results. Division of sclerotomes into loose cranial and dense caudal zones (sclerotomites) was observed in embryos aged 32 days (stage 13). The intervertebral disc developed from the dense zone of sclerotome and was well recognized in embryos aged 33 days (stage 14). At the end of fifth week (embryos at stage 15, 36 days) the annulus fibrosus and the nucleus pulposus were seen. The annulus fibrosus differentiated into lateral and medial zones. Within the lateral zone cells were arranged into circular rows. These rows were considered as the first stage of laminar structure. In further developmental stages the laminae occupied both zones of the annulus fibrosus. Conclusions. The intervertebral discs develop from the dense zone of the sclerotome which is evident in embryos at stage 13 (32 days). Discs differentiate in embryos aged 33 days, when the nucleus pulposus and annulus fibrosus are recognized. In embryos aged 36 days in the annulus fibrosus circular rows forming laminar arrangement are seen.